The effect of psychological contract breaches and self-efficacy on employee performance (Lighthouse Publishing, 2023)
PT Pegadaian (Persero) Lampung Area is a non-banking financial institution that provides credit to the public on mortgage laws in Indonesia. Psychological contract breaches are problems often found in companies where employees feel that the company violates promises made to contracts. In addition, employees' self-confidence level can influence the level of sound performance or vice versa. Performance appraisal is carried out transparently and objectively to see and evaluate employee performance. At the beginning of each financial year, PT Pegadaian (Persero) Lampung sets a Key Performance Indicator (KPI) for each work unit. The purpose of this study was to find out whether Psychological contract breaches and self-efficacy have a partial effect on employee performance at PT Pegadaian (Persero) Lampung area. Methods of data collection is using primary data. For the data analysis, we used simple linear regression and t-test; using the help of IBM SPSS version 25 software. The sample in this study was 125 respondents with a probability sampling technique and a simple random sampling method. The results of this study support the hypothesis that psychological contract breaches have a negative and significant effect on employee performance, and self-efficacy has a significant positive effect on employee performance at PT Pegadaian (Persero) Lampung Area.